ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA (INCOME SMOOTHING) PADA PERUSAHAAN MANUFAKTUR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - -, Hasbyanti - (Jurnal KIAFE, 2021)
Income smoothiin is defined asa practice by management to stabilize reported earnings. The study aims to identify and analyze the influence of firm size, profitability, financial leverage, and dividend payout ratio.on the opportunities for income smoothing practices. The data in this study used a purposive sampling method. The number of samples obtained as many as 15 companies with a total of 45 data. The sample is classified as income smoothing and non-income smoothing usin the Eckel Index. The result of thi study indicate that financial leverage has an effect on income smoothing practices, while firm size, profitability, and dividens payout ratio have no effect on income smoothing.Keyword: Income smoothing, Firm size, Profitability, Financial Leverage, and Dividend payout ratio.